Managing the partners in strategic alliances - Das, T. K. 1938- (Research in strategic alliances., 2021)
"Managing the Partners in Strategic Alliances is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances. Managing the Partners in Strategic Alliances contains contributions by leading scholars in the field of strategic alliance research. The 14 chapters in this volume deal with significant issues relating to the management of the partners in strategic alliances. These issues run the gamut from deterring deceitful behaviors, partner selection and control, interpartner learning, harmony, negotiation, tensions, and diversities, to partner management and alliance performance. The chapters contain empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on managing the partners in strategic alliances"--